The relationship between pelvis inclination, exercise and low back pain (LBP) during pregnancy [Vztah mezi bolestí zad, sklonem pánve a vhodnou pohybovou aktivitou v těhotenství] - Marcela Minaříková; Karel Jelen; Eva Tlapáková (Palacky University, 2011)
BACKGROUND: Pain in the lower region of the back and pelvis - also called "Low Back Pain" (LBP) - is very frequent during pregnancy. According to many authors it is a major complaint of more than half of all pregnant women; it causes mental and physical discomfort. The etiology of LBP during pregnancy is still not fully known. OBJECTIVE: The main aim of our research was to objectify the relationship between the presence of LBP, the training level of the postural muscles and the degree of the pelvic inclination of women in the third trimester of pregnancy. That is why the relationship between pelvic inclination and LBP occurrence is compared within the context of two groups - reasonable physically active as compared to physically inactive women. METHODS: Twenty-seven pregnant probands aged 20 - 35 years and in the second half of their third trimester were included in the experiment. All of them complained of pain in their lumbar spine and in the pelvicarea. They were divided into two groups: 14 physically inactive women and 13 physically active women, who have been performing physical activity for at least 135 minutes per week for at least 1 year before conception and for at least 90 minutes per week during pregnancy. The exercises were focused on the functioning of the postural system, e.g. yoga, Pilatespilatek and exercises by Mojzisova. We measured the inclination of the pelvis (using non-invasive anthropometric measuring) and observed the presence of pain in the selected area: clinically via the Patrick-Faber test and posterior pelvic pain provocation test and subjectively with the aid of a standardized LBP related survey. The statistical methods used were the t-test, the median and Wilcoxon-White test and the Spearman factor of serial correlations. RESULTS: We observed a statistically significant difference between the pelvic inclination of physically active and inactive women (using a t-test for non-pair values with a significance level of p = 0.01). Another significant difference was evident between the subjective pain sensation of regularly exercising and non-exercising women, which was proven by both the median and the Wilcoxon-White tests (p = 0.01). A significant relationship between pelvic inclination and the sensation of pain classified in a survey by means of a 1-10 scale was proven by the Spearman factor of serial correlations (p = 0.01). CONCLUSIONS: Using mathematical statistical methods, our study has proven the important role of physical activity during pregnancy - its relationship to pain sensation and to the degree of pelvic inclination. We consider these results to be very important, especially from the perspective of LBP prevention during pregnancy. [VÝCHODISKA: Bolesti v oblasti bederní páteře a pánve - tzv. "Low Back Pain" (LBP) – jsou v těhotenství velmi časté. Podle mnoha autorů si na tyto bolesti stěžuje více než polovina těhotných a přináší jim psychické i tělesné nepohodlí. Příčiny těchto bolestí během těhotenství nejsou stále ještě zcela známé. CÍLE: Hlavním cílem našeho výzkumu byla objektivizace vztahu mezi výskytem LBP, trénovaností posturálního svalstva a mírou inklinace pánve u žen ve třetím trimestru těhotenství. Proto byl vztah mezi sklonem pánve a výskytem LBP porovnán v rámci dvou skupin – přiměřené sportujících a nesportujících žen. METODIKA: Do experimentu bylo zahrnuto 27 těhotných probandek ve věkové kategorii 20 - 35 let, které byly ve druhé polovině třetího trimestru. Všechny probandky udávaly bolest v oblasti bederních segmentů páteře a pánve. Tento soubor byl rozdělen do dvou skupin: 14 nesportujících žen a 13 pravidelně sportujících žen, které se v průběhu těhotentsví účastnily komerčních cvičebních kurzů - minimálně 3 krát týdně po 45 minutách; cvičení byla zaměřena na aktivaci posturálních svalů (např. jóga, Pilates, cvičení dle Mojžíšové). Zjišťovali jsme sklon pánve (pomocí neinvazivního antropometrického měření) a sledovali jsme existenci bolesti v této oblasti, a to klinickým vyšetřením pomocí Patrik-Feberova testu a Provokačního testu posteriorní pánevní bolesti, a subjektivně pomocí standardizovaného dotazníku týkajícího se Low Back Pain. VÝSLEDKY: Statistická analýza pomocí t-testu pro nezávislé výběry prokázala významný rozdíl mezi sklonem pánve žen pravidelně sportujících a nesportujících. Analýza pomocí Wilcoxon-Whiteova i pomocí mediánového testu prokázala, že existuje významný rozdíl mezi subjektivním pociťováním bolesti u žen pravidelně cvičících a necvičících. Dále byl pomocí Spearmanova korelačního koeficientu prokázán statisticky významný vztah mezi sklonem pánve a cítěním bolesti stanovené v dotazníku škálou 1 – 10 bodů. ZÁVĚRY: Pomocí metod matematické statistiky naše studie potvrdila významnou roli tělesné aktivity v období gravidity ve vztahu k cítění bolesti a ke sklonu pánve. Tyto výsledky považujeme za velmi důležité zejména z hlediska prevence LBP u těhotných.]